2022
DOI: 10.1007/s10826-022-02305-1
|View full text |Cite
|
Sign up to set email alerts
|

Examining predictors of school belonging using a socio-ecological perspective

Abstract: Between the years of 2003–2015, the Programme for International Student Assessment (PISA) has identified a global trend signalling a decline in a sense of school belonging for secondary school students. Research has identified several factors that are positively related to school belonging, such as teacher support and academic motivation. However, little empirical research has been conducted to evaluate the relevant school belonging variables holistically and to assess their socio-ecological levels (e.g., stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 83 publications
2
5
0
Order By: Relevance
“…Whilst variously defined and operationalised in the literature (Askell- Williams et al, 2018;Libbey, 2004;Terrett et al, 2012), school belonging refers to a student's attachment, safety, and affiliation with their school (Allen et al, 2022;Goodenow & Grady, 1993;Terrett et al, 2012). Overall, it captures a student's sense of feeling valued and cared for at school (Ainley et al, 1986;Terrett et al, 2012).…”
Section: Conceptualisations Of School Belongingmentioning
confidence: 99%
“…Whilst variously defined and operationalised in the literature (Askell- Williams et al, 2018;Libbey, 2004;Terrett et al, 2012), school belonging refers to a student's attachment, safety, and affiliation with their school (Allen et al, 2022;Goodenow & Grady, 1993;Terrett et al, 2012). Overall, it captures a student's sense of feeling valued and cared for at school (Ainley et al, 1986;Terrett et al, 2012).…”
Section: Conceptualisations Of School Belongingmentioning
confidence: 99%
“…(2022a) clarified how conceptualizing belonging has evolved from an understanding centered on human motivation and interpersonal attachment (Baumeister & Leary, 1995;Maslow, 1954;Rogers, 1951) to more complex and broader interpretations that "consider the intrapersonal, temporal, cultural, environmental, and geographical contexts and experiences related to belonging" (Allen et al, 2022a(Allen et al, , p. 2805).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study contributes to the literature in two distinct ways: First, it qualitatively examines experiences of belonging by gathering data from teachers' daily lives. In discussion with Allen et al (2022a), who are prominent belonging researchers, Leary and Baumeister shared how most research over the past 25 years has involved questionnaire studies or lab experiments, with too little attention given to how people experience belonging in their daily lives (e.g., at work or school). Second, while later studies have investigated experiences of belonging among early-career teachers (Bjorklund Jr., 2023;Skott, 2019) and in co-teaching relationships (Pesonen et al, 2021), less is known about how teachers experience belonging in an urban lower secondary school setting.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, academic values are significant determinants of academic outcomes ( Jiang et al, 2020 ; Li et al, 2021 ). Past studies have shown that examination scores, school belongingness, engagement in learning, satisfaction with subjects and academic performance, academic self-concept, and psychological well-being of students are related to their academic values (e.g., Katrin et al, 2019 ; Jiang et al, 2020 ; Dou and Shek, 2021 ; Li et al, 2021 ; Wang et al, 2021 ; Allen et al, 2023 ). Nevertheless, striving for academic excellence would create much learning stress and academic anxiety to students ( Xu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%